2004
DOI: 10.1186/gb-2004-5-9-r68
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A microarray technology suitable for analyzing the expression of microRNAs and of other small RNAs was used to determine the microRNA expression profile during mouse-brain development and observed a temporal wave of gene expression of sequential classes of microRNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
240
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 717 publications
(255 citation statements)
references
References 55 publications
7
240
0
2
Order By: Relevance
“…Previous studies also suggested that miRNA alterations occur during neural stem cell differentiation and morphological development of the mammalian brain 29, 32. One member of our group also proved that a significant difference in miRNA expression pattern is a possible marker of anencephaly 17.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Previous studies also suggested that miRNA alterations occur during neural stem cell differentiation and morphological development of the mammalian brain 29, 32. One member of our group also proved that a significant difference in miRNA expression pattern is a possible marker of anencephaly 17.…”
Section: Discussionsupporting
confidence: 70%
“…Interestingly, at least half of the promoter regions for miRNAs are predicted to be in close proximity to CpG islands and their methylation frequency is predicted to be at least one order of magnitude higher than that of protein‐coding genes 12. New studies in human cell lines have also shown that folic acid deficiency and DNA hypomethylation can lead to the misexpression of miRNAs 26, 27, 28, 29. Against this background, a more thorough understanding of how folate deficiency contributes to the misexpression of miRNAs and their roles in NTDs should help us to clarify the mechanism behind miRNA regulation in NTDs.…”
Section: Introductionmentioning
confidence: 99%
“…In the construction of brain cell-specific miRNA array panels, 13 individual brain-enriched miRNAs and human 5S ribosomal RNA (5S rRNA) were spotted onto GeneScreen Plus nylon membranes using a Biomek® 2000 laboratory automation workstation (Beckmann, Fullerton, CA) and were crosslinked, baked, hybridized and probed according to the manufacturer's protocol (NEN® Research Products, Boston MA) [7,[10][11][12]. A guanidine isothiocyanate-and silica gel-based membrane total RNA purification system and miRNA isolation kit (PureLink™ Invitrogen, Carlsbad, CA) were used to isolate total small RNAs (5S rRNA, tRNA and miRNA) from magnesium-, aluminum-and iron-plus aluminum-sulfate treated HN cells.…”
Section: Footnote 1 -Experimental Detailsmentioning
confidence: 99%
“…Through their complementary base-pairing with the 3′ UTRs of target mRNA, miRNAs function in transcriptional processing or provide guidance for further mRNA modification [7][8][9][10][11][12][13][14][15][16][17]. The variable expression of miRNAs during cell growth and aging has suggested a role for miRNA in the regulation of gene expression during development and differentiation, and while human genomes encode several hundred different miRNAs, a significantly smaller sub-set is either enriched in the brain or specific to that organ [7,[10][11][12]. Although up-regulated miRNAs are generally regarded as negative regulators of these multiple processes, down-regulation of miRNA might be expected to enhance mRNA translation and thereby up-regulate the expression of specific genes.…”
mentioning
confidence: 99%
“…The set of microRNAs changed expression upon induction of cultured cells to neurogenic status. MicroRNAs are temporally regulated during brain devel opment (shown in rodents) [9].…”
mentioning
confidence: 99%